(untitled) (Nigerian Journal of Technology, 2025)
The African economy has experienced substantial growth in recent years, which has increased the number of businesses created annually in the region, and this can translate into significant economic growth over the next few years. With technological advancements and digitization, African businesses can optimize their operations and improve efficiency by leveraging new and disruptive technology for innovation and development. This study discusses emerging technologies like the Internet of Things and Blockchain. It extensively analyzes the use of Radio Frequency Identification systems in Supply Chain Management as a case study. In addition, it also proposes a blueprint for leveraging emerging technologies and discusses some of the challenges these new technologies may bring. Furthermore, we highlighted how some new technologies could improve efficiency for African businesses when successfully integrated into creating business models and discussed examples of African businesses already on this path. Africa must embrace technology for economic transformation, and African businesses are tools to achieve this transformation.